Geographic distribution and spatial differentiation in the color pattern of abdominal stripes of the Neotropical stingless bee Melipona quadrifasciata (Hymenoptera: Apidae) - Batalha-Filho,Henrique (2009)
Melipona quadrifasciata Lepeletier, 1836, regionally known as "mandaçaia", has been traditionally divided in two distinct subspecies: M. quadrifasciata anthidioides and M. quadrifasciata quadrifasciata. The main difference between the subspecies refers to the yellow metasomal stripes which are continuous in M. q. quadrifasciata and discontinuous in M. q. anthidioides. This study investigated the geographic differentiation in the metasomal stripes and characterized the restriction sites in the mtDNA of both chromatic types. Specimens from 198 localities were examined, and the variation observed in the pattern of stripes was grouped into distinct classes. The distribution pattern found in the present work agrees with the previously reported pattern: M. q. quadrifasciata inhabits the southern portion of the distribution, from Misiones, Argentina, southeastern Paraguay and Rio Grande do Sul to southern São Paulo, and M. q. anthidioides ranges from northeastern São Paulo to the northern Diamantina Plateau, Bahia, and westwards to the central portion of the Goiás state. It is documented for the first time the occurrence of two populations with continuous stripes inhabiting disjunct areas in relation to M. q. quadrifasciata - one in northern Minas Gerais and another in northeastern Bahia and Sergipe. The data of RFLP showed two restriction patterns, one present in M. q. quadrifasciata, and another in M. q. anthidioides and in populations with continuous metasomal stripes from northern Minas Gerais and northeastern Bahia and Sergipe. The observed patterns of geographic differentiation of M. quadrifasciata suggests the occurrence of repeated events of geographical isolation, followed by range expansion, that occurred probably during the cycles of climatic changes in the Pleistocene.